Adaptation of number experiment method of solution to mathematical method of solution to mathematical model of firefighting centrifugal pump - Sutorma Игорь Иванович; Lifanov А.В. (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
The results of number experiments for adaptation the method of final volumes to mathematical modeling of hydrodynamic processes in fighting centrifugal pump are given in the article.